2016
DOI: 10.1097/md.0000000000003688
|View full text |Cite
|
Sign up to set email alerts
|

Serum Clusterin as a Prognostic Marker of Chronic Spontaneous Urticaria

Abstract: A substantial proportion of patients with chronic spontaneous urticaria (CSU) are refractory to antihistamines. However, identifying the subpopulation whose urticaria is not completely controlled by antihistamines remains difficult. The response of autologous serum skin test (ASST), a clinical test for the detection of basophil histamine-releasing activity upon autoantibodies or autoreactive stimulation, has been suggested as a potential predictor in the control of urticaria. We sought to identify proteins tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Patients with autoantibodies may have severe urticaria symptoms more than patients without autoantibodies, but recent studies have shown that ASST was not associated with disease severity [1213]. Serum vitamin D and clustering levels are associated with disease severity in CSU [141516]. Moreover, serum concentrations of interleukin (IL)-17, IL-23, and tumor necrosis factor-α are associated with CSU disease activity and ASST [17].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with autoantibodies may have severe urticaria symptoms more than patients without autoantibodies, but recent studies have shown that ASST was not associated with disease severity [1213]. Serum vitamin D and clustering levels are associated with disease severity in CSU [141516]. Moreover, serum concentrations of interleukin (IL)-17, IL-23, and tumor necrosis factor-α are associated with CSU disease activity and ASST [17].…”
Section: Introductionmentioning
confidence: 99%
“…Refractory CU was defined as patients whose urticaria symptoms were not controlled by increasing the antihistamine dose to 4-fold within 3 months. In contrast, patients who responded well to antihistamines were classified as having responsive CU [20] . The required antihistamine doses used to control urticaria symptoms for a subsequent 3 months after enrollment were calculated as the equivalent dose (mg/day) of loratadine.…”
Section: Assessment Of Urticaria Activity Score and Therapeuticmentioning
confidence: 99%
“…Currently, clusterin is attracting scientific attention in the context of neoplasia mechanisms as well. Elevated serum clusterin levels have been observed in the course of many different human disorders, such as diabetes [53], coronary heart disease [53], psoriasis [54], chronic spontaneous urticaria [55], septic shock [56], and several neoplastic diseases, e.g., colorectal cancer [57] or prostate cancer [58]. On the other hand, a decreased serum clusterin level has been proven during osteoarthritis [59], systemic lupus erythematosus [60], sepsis [61], human hepatocellular carcinoma [62], and esophageal squamous cell carcinoma [63].…”
Section: Preinfective Stage Of T Spiralis T Britovi and T Pseudomentioning
confidence: 99%